Starvation after infection restricts enterovirus D68 replication. Issue 1 (2nd January 2023) - Jassey, Alagie; Wagner, Michael A.; Galitska, Ganna; Paudel, Bimal; Miller, Katelyn; Jackson, William T.
ABSTRACT: Enterovirus D68 (EV-D68) is a respiratory pathogen associated with acute flaccid myelitis, a childhood paralysis disease. No approved vaccine or antiviral treatment exists against EV-D68. Infection with this virus induces the formation of autophagosomes to enhance its replication but blocks the downstream autophagosome- lysosome fusion steps. Here, we examined the impact of autophagy induction through starvation, either before (starvation before infection, SBI) or after (starvation after infection, SAI) EV-D68 infection. We showed that SAI, but not SBI, attenuated EV-D68 replication in multiple cell lines and abrogated the viral-mediated cleavage of host autophagic flux-related proteins. Furthermore, SAI induced autophagic flux during EV-D68 replication and prevented production of virus-induced membranes, which are required for picornavirus replication. Pharmacological inhibition of autophagic flux during SAI did not rescue EV-D68 titers. SAI had the same effect in multiple cell types, and restricted the replication of several medically relevant picornaviruses. Our results highlight the significance of autophagosomes for picornavirus replication and identify SAI as an attractive broad-spectrum anti-picornavirus strategy. Abbreviations: BAF: bafilomycin A1 ; CCCP: carbonyl cyanide m-chlorophenylhydrazone; CQ: chloroquine; CVB3: coxsackievirus B3; EV-D68: enterovirus D68; hpi: hour post-infection; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MOI: multiplicity of infection; NSP2B: nonstructural protein 2B; PV: poliovirus; RES: resveratrol; RV14: rhinovirus 14; SAI: starvation after infection; SBI: starvation before infection; SNAP29: synaptosome associated protein 29; SQSTM1/p62: sequestosome 1; TFEB: transcription factor EB.